2009
DOI: 10.1177/0963662508096782
|View full text |Cite
|
Sign up to set email alerts
|

Research and reporting on the development of sex in fetuses: gendered from the start

Abstract: Research into human genetics has been expanding rapidly and most people learn about that research from mass media. Because prior research finds gender bias in aspects of both science and the media, we investigate the messages presented to the public concerning the relationship between biology and gender, taking as a case research on the genetic development of sexual difference before birth. We examine both the science that is getting media attention and the form that coverage takes. We find that gendered assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Gender biases have been observed in mass media's coverage of many health topics, including cancer (Andsager & Powers, 2001;Arrington & Goodier, 2004;Lantz & Booth, 1998), HIV/AIDS (Hoffman-Goetz, Friedman, & Clarke, 2005;Myrick, 1999), menopause (Kaufert & Lock, 1997), and medical research (Dingel & Sprague, 2010;Petersen, 1999). Such biased media coverage further perpetuates traditional gender roles (Kline, 2006).…”
Section: Gender Bias In Media Coverage Of Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender biases have been observed in mass media's coverage of many health topics, including cancer (Andsager & Powers, 2001;Arrington & Goodier, 2004;Lantz & Booth, 1998), HIV/AIDS (Hoffman-Goetz, Friedman, & Clarke, 2005;Myrick, 1999), menopause (Kaufert & Lock, 1997), and medical research (Dingel & Sprague, 2010;Petersen, 1999). Such biased media coverage further perpetuates traditional gender roles (Kline, 2006).…”
Section: Gender Bias In Media Coverage Of Healthmentioning
confidence: 99%
“…For instance, phrases such as "lacking," "left behind in the race," and "missing the boat" were used to describe women (Petersen 1999, p. 176). In a more recent study of the coverage of genetic research on fetal sex development in newspapers and magazines, Dingel and Sprague (2010) found that the inherent superiority of men was conveyed as a theme.…”
Section: Gender Bias In Media Coverage Of Healthmentioning
confidence: 99%